2014
DOI: 10.1186/1475-2891-13-115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary creatine supplementation on systemic microvascular density and reactivity in healthy young adults

Abstract: BackgroundDietary creatine supplementation (CrS) is a practice commonly adopted by physically active individuals. However, the effects of CrS on systemic microvascular reactivity and density have never been reported. Additionally, CrS is able to influence blood levels of homocysteine, resulting in presumed effects on vascular endothelial function. Thus, we investigated the effects of CrS on the systemic microcirculation and on homocysteine levels in healthy young individuals.MethodsThis open-label study was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 67 publications
1
30
3
Order By: Relevance
“…It is noteworthy that the capillary densities in all of the groups of the present study appeared to be significantly higher than those observed in omnivores of the same age‐group in another study conducted by our group , suggesting that vegans have a higher degree of tissue perfusion than omnivorous subjects.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…It is noteworthy that the capillary densities in all of the groups of the present study appeared to be significantly higher than those observed in omnivores of the same age‐group in another study conducted by our group , suggesting that vegans have a higher degree of tissue perfusion than omnivorous subjects.…”
Section: Discussioncontrasting
confidence: 60%
“…Although neither placebo nor CrS was able to alter the vitamin B‐12 levels in normo‐ or hyperhomocysteinemic vegan subjects, these levels were marginally but significantly lower among the hyperhomocysteinemic vegan subjects. Our volunteers did not show any hypothyroidism signs despite this micronutrient deficiency being a risk of vegan diets, and CrS did not change the T3 and T4 serum levels as it did with the omnivorous subjects in our previous study .…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations